Beehive Briquette for maintaining desired microclimate in Goat Shelters during winter - Kumar, Arvind; Chaudhary, U B; Kumar, Ravindra; Ramachandran, N; Arif, Mohd. (Indian Farming, 2020)
Extremely cold weather condition adversely affects the growth performance of goats especially the young ones. The climatic zones where the minimum temperature falls below 10Â°C needs additional protection by use of gunny bags, thatch panels etc. Even after the gunny bags and thatch panels, the occurrence of pneumonia and other respiratory problems are being observed in newborn kids and kids having lower birth weight particularly in highly prolific and small sized goats. For such conditions, beehive briquette can easily be used for maintaining goat sheds with required microclimate in rural areas at low cost as the biomass is available locally and does not require any costly equipment. Therefore, the goat keepers in rural areas shall use these briquettes to have warmer microclimate for rearing young kids during inclement cold weather conditions.